Essential oils from oleoresins of Protium spp. of the Amazon region - Ramos, Mônica Freiman de Souza; Siani, Antonio C.; Tappin, Marcelo Raul Romero; Guimarães, Anderson Cavalcante; Ribeiro, José Eduardo Lahoz da Silva (Flavour and Fragrance Journal, 2000)
The essential oils of six species of Protium (Burseraceae), collected near Manaus, Amazon, were extracted by hydrodistillation and analysed by GC-MS. Resins from four species were collected yearly, and two species were represented by more than one tree. All six oils were found to be entirely monoterpenoid in constitution and were characterized by the predominance of p-cymene and α- and β-phellandrene. The composition of fresh exudates is associated with increasing content of α-pinene and unsaturated p-menthanes. Copyright © 2000 John Wiley & Sons, Ltd.
Keywords: Alpha Phellandrene; Beta Phellandrene; Essential Oil; Para Cymene; Para Menthane; Pinene; Plant Extract; Protium Extract; Resin; Terpenoid; Unclassified Drug; Chemical Analysis; Chemical Composition; Distillation; Drug Isolation; Gas Chromatography; Hydrolysis; Mass Spectrometry; Nonhuman; Plant; Protium; Tree; Burseraceae; Protium